Dampak Meningkatnya Kompetensi Dosen dan Motivasi Belajar Terhadap Prestasi Belajar Mahasiswa - Muhammad Rizal Syaifuddin; Dhiah Fitrayati (Jurnal Pendidikan Ekonomi (JUPE), 2021)
The purpose of this study was to determine the effect of lecture competence and learning motivation on the learning achievement of 2017 Economics Education Department Student at State University of Surabaya. This research is an associative quantitative research. Respondents were 167 students. The results of this research indicate lecturer competence and learning motivation have a positive and significant effect either partially or simultaneously on student learning. The conclusion of this study is that high learning achievement can be obtained by increasing the student's own learning motivation as an internal factor and the competence possessed by the lecturers also helps improve learning achievement from the external side, so that the two factors are expected to help students achieve high learning achievement